Pharmacokinetics and Tissue Levels of Pantoprazole in Neonatal Calves After Intravenous Administration - Olivarez, Jeff D.; Kreuder, Amanda J.; Tatarniuk, Dane M.; Wulf, Larry W.; Dembek, Katarzyna A.; Mochel, Jonathan P.; Smith, Joe S. (Frontiers in Veterinary Science, 2020)
Background: Neonatal calves are at risk of developing abomasal ulceration, but there is a lack of pharmacokinetic data for potential anti-ulcerative therapies, such as pantoprazole, in ruminant species. Objective: The study objectives were to estimate plasma pharmacokinetic parameters for pantoprazole in neonatal dairy calves after intravenous (IV) administration. A secondary objective was to quantify the concentrations of pantoprazole in edible tissues after IV dosing. Methods: Pantoprazole was administered to 9 neonatal Holstein calves at a dose of 1 mg/kg IV. Plasma samples were collected over 24 hours and analyzed via HPLC-MS for determining pantoprazole concentrations. Pharmacokinetic parameters were derived via noncompartmental analysis. Tissue samples were collected at 1, 3, and 5 days after administration and analyzed via HPLC-MS. Results: Following IV administration, plasma clearance, elimination half-life, and volume of distribution of pantoprazole were estimated at 4.46 mL/kg/min, 2.81 hr, and 0.301 L/kg respectively. The global extraction ratio was estimated at 0.053 ± 0.015. No pantoprazole was detected in the edible tissues 1, 3, or 5 days after administration. A metabolite, pantoprazole sulfone was detected in all the edible tissues 1 and 3 days after administration. Conclusion: The reported plasma clearance for pantoprazole is less than that reported for alpacas but higher than reported in foals. The elimination half-life in calves appears to be longer than observed in foals and alpacas. While pantoprazole sulfone was detected in the tissues after IV administration, further research is needed as to the metabolism and potential tissue accumulation of other pantoprazole metabolites in calves. Future pharmacodynamic studies are necessary to determine the efficacy of pantoprazole on abomasal acid suppression in calves.